2019
DOI: 10.1111/nyas.14135
|View full text |Cite
|
Sign up to set email alerts
|

Gpr126 (Adgrg6) is expressed in cell types known to be exposed to mechanical stimuli

Abstract: GPR126 (ADGRG6) is an adhesion G protein–coupled receptor that plays an important role in a variety of tissues/organs, such as heart, sciatic nerve, cartilage, and ear. Moreover, GPR126 (ADGRG6) mutations are associated with human diseases, like adolescent idiopathic scoliosis, lung disease, bladder cancer, and intellectual disability. Despite its clinical importance, it remains elusive how GPR126 is activated and mediates signal transduction and what cellular processes depend on GPR126 signaling. Here, we gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 55 publications
5
35
0
Order By: Relevance
“…We found small changes in cAMP in the gain‐ and loss‐of‐function experiments and that treatment with the putative ADGRG6 agonist Collagen IV (Paavola et al, 2014) did not change cellular cAMP levels. However, activation of this GPCR may require mechanical activation, as it is expressed in cell types that undergo mechanical stress (Musa et al, 2019) and activated mechanically by laminin‐211 (Petersen et al, 2015). Further work examining the relationship of ADGRG6 and other factors involved in cAMP signalling and proliferation in PASMCs, and perhaps other smooth muscle cells, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…We found small changes in cAMP in the gain‐ and loss‐of‐function experiments and that treatment with the putative ADGRG6 agonist Collagen IV (Paavola et al, 2014) did not change cellular cAMP levels. However, activation of this GPCR may require mechanical activation, as it is expressed in cell types that undergo mechanical stress (Musa et al, 2019) and activated mechanically by laminin‐211 (Petersen et al, 2015). Further work examining the relationship of ADGRG6 and other factors involved in cAMP signalling and proliferation in PASMCs, and perhaps other smooth muscle cells, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…While comparison of the transcriptional changes in different tissues as was presented here must be interpreted with great caution, the possibility of myotoxicity induced by a PrP-based agent should not be discounted. Early studies suggested that Adgrg6 is expressed in muscle tissue [45], but a recent study objected that Adgrg6 detected in muscle homogenate derived from endothelial cells instead of muscle cells [46]. Thus, it remains unclear whether the toxic effect of PrP is mediated by Adgrg6 or by other interaction partners.…”
Section: Plos Onementioning
confidence: 99%
“…S1C, online only). In addition, miR‐27a and miR‐27b have previously been associated with physiology and pathophysiology of tissues and organs in which Gpr126 is expressed, including heart, bladder, vasculature, and salivary gland . Moreover, miR‐27a, miR‐27b, and Gpr126 are shear stress–regulated in HUVEC cells …”
Section: Resultsmentioning
confidence: 99%
“…miR‐27b and Gpr126 are both expressed during heart development and in endothelial cells, are both shear stress–regulated, and associated with cognitive impairment or intellectual disability, as well as bladder cancer . In addition, it is known that Gpr126 is expressed in the salivary gland, lung, and kidney, while miR‐27b is associated with non‐small cell lung cancer, clear cell renal cell cancer, and adenoid cystic carcinoma of the salivary glands . Moreover, miR‐27b has been shown to regulate the expression of delta‐like ligand 4 ( Dll4 ), which activates Notch signaling, an established regulatory pathway of Gpr126 expression in HUVECs and the endocardium of the developing heart …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation